Strategi Pemasaran Pendidikan Berbasis Media Sosial di SDN 060816 Medan - Yusnia Meha; Anisah Anisah; Nabilah Ulfiyah; Siddiq Permadi; Tulus Abdul Wahid,; Mia Audina Naibaho; Aidatul Fauziah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
The obligation of educational institutions is not only to make various efforts such as the use of information and communication technology, procurement of educational facilities and infrastructure, quality improvement or so on. , so that what is needed by educational institutions is in accordance with what is currently desired by the community, so as to produce satisfaction with each other. Because without being marketed or communicated, it will be useless and left behind which leads to the death of the educational institution that loses to educational institutions others, who are more ready to compete and act quickly in winning hearts and becoming the community's favorite school. carried out at SDN 060816, which is on Jalan Sutrisno, Medan District, Medan City Area. It was carried out for 1 day. The research approach used was qualitative research, with descriptive methods. This study used observation, interview and documentation techniques in the data collection process. The results of observations and interviews showed that the social media-based education marketing strategy at SDN 060816, educational institutions are very eager to market their school in order to make their school a school that is widely known by the public. So that people are interested in sending their children to the school. Keywords: Educational marketing strategy, Social media.